PEMBENTUKAN WADAH SUBAK-GDE DI DAERAH IRIGASI KEDEWATAN KABUPATEN GIANYAR - Windia, W.; Suamba, K. (Buletin Udayana Mengabdi; Vol 11 No 1 (2012): Volume 11 No.1 – April 2012, 2012)
Basically now, the water available is scarcer. Meanwhile, the population growth that occurs so fast, which is followed by increasing of public prosperity and development of other sectors beyond agricultural sector, causing the increase in water need, both quantitatively and qualitatively. That is why the water need is very competitive among sectors. Generally, in terms of water need for farmers, it is often defeated by the other sectors (especially by the tourism sector). The same situations is felt by subak farmers who get water from the Kedewatan Dam, in Sub Regency of Ubud, Regency of Gianyar. Some international hotels in the head of the dam freely take water from the river, and moreover in the end of the dam, rafting activities and the Drinking Water of The Government of Denpasar Company often borrow water from the dam. Therefore, the water available for the subaks is frightened. Based upon such conditions, it is very important to motivate all heads of subaks getting water from the Kedewatan Dam to organize themselves in the institution of subak coordination body (subak-gde). Anyhow, that organization is important to strengthen the subak position in their negotiation activities with the outsider. In these community service activities, basically all subak members very much agree to make the higher subak coordination body (subak-gde).